1978
DOI: 10.2337/diab.27.8.810
|View full text |Cite
|
Sign up to set email alerts
|

Diabetes Screening Using a Quantitative Urine Glucose Method

Abstract: Sensitivity and specificity of three methods (random urine glucose (RUG) > 25 mg. per deciliter; positive Clinitest; and random plasma glucose (RPG) > 140, > 120, and > 100 mg. per deciliter) for detecting the unknown diabetic were compared. In 1,952 screenees, RUG of 96.7 per cent was 3 to 25 mg. per deciliter (normoglucosuria), RUG of 2.0 per cent was 26 to 100 mg. per deciliter (moderate hyperglucosuria), and of 1.3 per cent was > 100 mg. per deciliter (marked hyperglucosuria). Twenty-five randomly selected… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1986
1986
2013
2013

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 6 publications
0
1
0
Order By: Relevance
“…A sensitivity of 35.3% and a specificity of 99.7% were reported by West and Kalbfleisch. 26 In a prospective diagnostic study collecting urine from fasted subjects, Davidson et al 27 reported a sensitivity of 74% and a specificity of 86% whereas Friderichsen and Maunsbach 28 reported a sensitivity of 20.8%, specificity of 99.14% and a PPV of 46.88%. We are aware that urinalysis is not sufficiently sensitive to detect a high proportion of persons with diabetes and has the potential to find more false negatives than blood screening, but, nevertheless, these mass screening data suggest that, in a developing country such as Trinidad and Tobago, childhood diabetes of all types can be identified by glycosuria.…”
Section: Discussionmentioning
confidence: 99%
“…A sensitivity of 35.3% and a specificity of 99.7% were reported by West and Kalbfleisch. 26 In a prospective diagnostic study collecting urine from fasted subjects, Davidson et al 27 reported a sensitivity of 74% and a specificity of 86% whereas Friderichsen and Maunsbach 28 reported a sensitivity of 20.8%, specificity of 99.14% and a PPV of 46.88%. We are aware that urinalysis is not sufficiently sensitive to detect a high proportion of persons with diabetes and has the potential to find more false negatives than blood screening, but, nevertheless, these mass screening data suggest that, in a developing country such as Trinidad and Tobago, childhood diabetes of all types can be identified by glycosuria.…”
Section: Discussionmentioning
confidence: 99%